Induction of Erythrocyte Shrinkage by Omeprazole. Issue 3 (3rd August 2020) - Naveed, Ayesha; Jilani, Kashif; Siddique, Abu Bakar; Akbar, Muhammad; Riaz, Muhammad; Mushtaq, Zahid; Sikandar, Muhammad; Ilyas, Sajida; Bibi, Ismat; Asghar, Asma; Rasool, Ghulam; Irfan, Muhammad
Omeprazole, a proton pump inhibitor blocks the H + /K + -ATPase channels of gastric parietal cells. It is used for the treatment of peptic ulcer. Prolonged use of omeprazole may involve in inducing anemia. The key marker of eryptosis includes membrane blebbing, cell shrinkage and phosphatidylserine (PS) exposure at the cell surface. In current study, the eryptotic, oxidative as well as hemolytic effects of therapeutical doses (0.5, 1 and 1.5 µM) of omeprazole were investigated after exposing erythrocytes for 48 hours. Investigation of eryptosis was done by cell size measurement, PS exposure determination and calcium channel inhibition. As a possible mechanism of omeprazole induced eryptosis, oxidative stress was investigated by determining the catalase, glutathione peroxidase and superoxide dismutase activities. Similarly, necrotic effect of omeprazole on erythrocytes was also evaluated through hemolysis measurement. Results of our study illustrated that 1.5 µM of omeprazole may induce significant decrease in superoxide dismutase, glutathione peroxidase and catalase activities as well as triggered the erythrocytes shrinkage, PS exposure and hemolysis. Role of calcium was also confirmed in inducing erythrocyte shrinkage. It is concluded that the exposure of erythrocytes with 1.5 µM omeprazole may enhance the rate of eryptosis and hemolysis by inducing oxidative stress.